Research of Model Scale Seawater Intrusion using Geoelectric Method - Supriyadi; Yulianto, Agus; Haryanto, Andi (IPTEK The Journal for Technology and Science, 2025)
A depth experience and knowledge are needed in analyzing the prediction of seawater intrusion. We report here a physical modelling for monitoring the model scale of seawater intrusion. The model used in this research is glass basin consists of two parts; soil and seawater. The intrusion of seawater into soil in the glass basin is modelled. The results of two-dimensional inversion by using software Res2DInv32 showed that the monitoring of seawater intrusion, in soil model scale, can be detected by using Schlumberger configuration resistivity method. The watering process of freshwater into soil caused the electric resistivity value decreased. This phenomenon can be seen from the transition of the resistivity pseudo section before and after the watering process using different cumulative volume of freshwater in different soil. After being intruded by the seawater, the measured soil resistivity is 2.22 ohm meter to 5.69 ohm meter which means that the soil had been intruded.